EXPERIMENTAL COMPUTER SCIENCE. - Feitelson, Dror G. (Communications of the ACM, 2007)
The article discusses the need for greater experimentation in computer science. Unlike other sciences, where theory and experimentation complement one another, computer science has traditionally placed a greater emphasis on theory. The increasing complexity of computing renders this approach obsolete, though. Empirical studies are required to better understand both technology and how users interact with it. The first ever workshop on Experimental Computer Science held in San Diego, California attests to growing interest in the field.